2008
DOI: 10.1007/s00432-008-0403-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CCR6 expression level and aggressiveness of prostate cancer

Abstract: Expression levels of CCR6 in PCA were associated with clinical and pathologic features of more advanced and aggressive prostate cancer. Thus, CCR6 may directly or indirectly be involved in tumor progression and should be evaluated as novel candidate target molecule for specific treatment interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 25 publications
3
31
0
1
Order By: Relevance
“…However, motility and invasiveness abilities of HCCLM6 cells were maintained in untreated HCCLM6 cells. The underlying mechanisms are attributed to the blockade of the activation of CCR6 pathway, which further inhibit the expression of invasion and metastasis-related genes and proteins [24]. The results confirmed that both nucleolin and CCR6 act as an appropriate target to inhibit the migration and invasion of HCC.…”
Section: Discussionsupporting
confidence: 72%
“…However, motility and invasiveness abilities of HCCLM6 cells were maintained in untreated HCCLM6 cells. The underlying mechanisms are attributed to the blockade of the activation of CCR6 pathway, which further inhibit the expression of invasion and metastasis-related genes and proteins [24]. The results confirmed that both nucleolin and CCR6 act as an appropriate target to inhibit the migration and invasion of HCC.…”
Section: Discussionsupporting
confidence: 72%
“…52 The profound increase in CCL20 expression (ϳ25ϫ) and its receptor CCR6 (ϳ5ϫ) is of particular significance as increased CCR6 expression has been associated with advanced and aggressive PCa and CCL20/CCR6 have also been suggested as novel treatment target molecules for PCa. 31 The increased expression of CCL8, CCR5, and CCR2 in the AROMϩ tissues is also particularly significant (increased ϳ10ϫ, ϳ3ϫ, and ϳ4ϫ, respectively). Although the role of CCL8 in the prostate is unknown, this chemokine elicits its effects by binding to the receptors CCR5 and CCR2.…”
Section: Estrogens Prostatitismentioning
confidence: 97%
“…Of particular significance were significant increases in the expression of CCL20, CCL8, CCR6, CCR5, and CCR2, all of which have been implicated in the development of PCa. 31,32,33 …”
Section: Chronic Inflammation As a Cause Of Prostatic Premalignancymentioning
confidence: 99%
“…Members of the CCR family are also used by tumor cells to spread to specific tissues such as the skin, the gut and the liver. CCR6 plays a role in organ selective liver metastasis of colorectal cancer [107,108]. The skin-homing receptors CCR4 and CCR10 were found expressed together with CCR3 in cutaneous lymphoma [109][110][111].…”
Section: Tumor Cell Invasion and Migration To Distant Organsmentioning
confidence: 99%